Direct Electron Transfer of Hemoglobin on Manganese III Oxide-Ag Nanofibers Modified Glassy Carbon Electrode - Masoud Negahdary; Gholamreza Mazaheri; Somyyeh Rad; Mohammadreza Hadi; Roya Malekzadeh; Mohammad Mahdi Saadatmand; Saeed Rezaei-Zarchi; Fariba Pishbin; Mojdeh Khosravian-hemami (International Journal of Analytical Chemistry)
We investigated the electrochemical behavior of hemoglobin by glassy carbon electrode modified with Mn2O3-Ag nanofibers. The Mn2O3-Ag nanofibers were used as facilitator electron transfer between Hb and glassy-carbon-modified electrode. The Mn2O3-Ag nanofibers are studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The hemoglobin showed a quasireversible electrochemical redox behavior with a formal potential of −49 mV (versus Ag/AgCl) in 0.1 M potassium phosphate buffer solution at pH 7.0. The designed biosensor possesses good stability and reproducibility and achieves 95% of the steady-state current in less than five seconds.